German Chronicle „Annaberger Annalen Über Litauen und deutsch - litauische Beziehungen “ is a Quarter of a Century Old - Hermann, Arthur (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English] The subject of the research is the chronicle “Annaberger Annalen über Litauen und deutsch-litauische Beziehungen“ (“Anaberg’s Annascript on Lithuania and German-Lithuanian Relations”), which is published in Germany since year 1993. Over the period of 25 years, 26 volumes have been traditionally and digitally published, consisting of 318 articles authored by 221 researchers and covering 7440 pages. Prepared and published by an initiator group: Arthur Hermann, Annemarie Lepa, dr. Christina Nikolajew ir dr. Lina Pilypaitytė. The clients are Baltischer Christlicher Bund (Bonn) and the Litauisches Kulturinstitut (Lampertheim). There is a tradition of publishing scientific articles in two thirds of each volume and to have onethird for publications of a different kind. What is more, the part of scientific articles is constantly increasing. In the past, the relationship between the German Ordinance and the Grand Duchy of Lithuania has been further explored whilst today it is more often written about the 19th–20th centuries of German-Lithuanian relations and other issues concerning people of East Prussia, Klaipėda region and heritage. There are about 100 subscribers of the annual edition of the printed version and thousands of the digital version. The future of the chronicle is not clear due to financing problems.